2021
DOI: 10.1093/tas/txab112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary chromium propionate and space allowance on performance and carcass responses of growing-finishing pigs

Abstract: In a 72-day trial, 256 pigs (Line 600 × 241, DNA Columbus, NE) were used to determine the effect of dietary Cr (Cr propionate; Kemin Industries, Des Moines, IA) and physical space restriction on performance and carcass characteristics of finishing pigs. Pens were blocked by initial weight and randomly assigned to treatments with eight pigs per pen and eight pens per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of Cr (control and Cr propionate, 200 µg/kg added Cr) and space allowan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A total of 5977 published studies were retrieved using the aforementioned methods. After screening and eliminating duplicate studies based on the inclusion and proposed criteria mentioned earlier, we selected 35 studies for this meta-analysis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], which involved 4366 pigs. The details of these studies can be found in Table A2 of Appendix A .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5977 published studies were retrieved using the aforementioned methods. After screening and eliminating duplicate studies based on the inclusion and proposed criteria mentioned earlier, we selected 35 studies for this meta-analysis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], which involved 4366 pigs. The details of these studies can be found in Table A2 of Appendix A .…”
Section: Resultsmentioning
confidence: 99%